PENERAPAN SISTEM KEUANGAN DESA (SISKUEDES) DALAM MENINGKATKAN PENATAUSAHAAN DESA SUKOHARJO KECATAMAN WILANGAN KABUPATEN NGANJUK - Nuke Yuandika; Indrian Supheni; Budiono Budiono; Suwandi Suwandi (JURNAL MUTIARA AKUNTANSI, 2020)
The purpose of this study is (1) to find out the application of the village financial system (SISKEUDES) in sukoharjo village, wilangan district, nganjuk district. (2) to find out the implementation of the village financial system (SISKUEDES) in improving administration in sukoharjo village, wilangan ngnajuk district. This type of research is a qualitative approach with descriptive methods. The data used are primary in the form of observations, interviews, and secondary data. The information obtained was the village secretary and village treasurer. The results showed that Sukoharjo Village, Wilangan District, Nganjuk District had implemented a village financial system or SISKUEDES in improving administration in Sukoharjo Village, Wilangan District, Nganjuk District, covering the stages of planning, administration, reporting, and accountability by Permendagri No. 113 of 2014.